Rehabilitación de una casa en La Clota - EMBT (2000)
En Valld'Hebrón, Barcelona, España 1997/1999. Premio FAD 1999
Keywords: MIRALLES, ENRIC; TAGLIABUE, BENEDETTA; REHABILITACION; PREMIOS; ESPAÑA; BARCELONA